PENDAMPINGAN PEMBUATAN WEBSITE SISTEM KEPENDUDUKAN (SISPENDUK) DI DESA TANJUNG MANIS KECAMATAN ANYAR SERANG BANTEN - Ulfi Jefri; Allfian Rahma Putra; Ayu Navita Maulidya; Rachma Fithri Aulia (STAI Darul Qalam Tangerang, 2022)
The study aims to develop a village website on student project (KKM) University of Bina Bangsa in developing the field of information technology that is worthy of use. As a form of student outreach to the community in the village Tanjung Manis and provide benefits to the local population's administrative data. Research shows that the developed websites are valid and worthy of use by accessing citizen data, by automatically and more effectively mailing, and by being able to determine the number of rural residents. So it can be concluded that the websites developed are valid and worthy of use in the village Tanjung Manis registry process